THEORETICAL FOUNDATIONS AND MODERN TRENDS IN ENSURING POPULATION EMPLOYMENT - Shukurov, Ilkhom (THE INNOVATION ECONOMY, 2026)
This article highlights the socio-economic essence of employment, its inextricable connection with the labor market, and development trends in the context of globalization. It is substantiated that employment, as an activity of the population aimed at generating income, is an important factor ensuring the stability of the economic system. It also analyzes the interaction of labor market participants, the balance of supply and demand, and issues of personnel training and employment growth in an innovative economy. The theoretical and methodological significance of labor market segmentation is revealed, and the necessity of improving employment policy and strengthening social protection through it is substantiated.